Efficacy of commercial shrimp farmbioremediators in removing ammonia inmicrocosm experiments - Ghosh, Shubhadeep; Sasmal, Debasis; Abraham, T Jawahar (Indian Journal of Fisheries, 2011)
The efficacy of two commercialaquaculture bioremediators to removeammonia was tested under laboratoryconditions. The bioremediators werecapable of removal of total ammoniacalnitrogen (TAN) to the tune of 86 - 90%(max) at 1-3 ppm initial level of ammonia(NH3) and the removal rate decreasedthereafter. Significant differences innitrite (NO2) levels in treated and controltanks were observed probably due to thedifferences in the levels of residentnitrifying bacteria that utilize NH3 andoxidize it to NO2. The nitrate levelsincreased in all the treatment tanks, butshowed a general decreasing trend incontrol tanks. Among the tanks withvaried NH3 concentrations, the levels ofNO3 between the control and treatmenttanks differed insignificantly (P>0.05)The results of the present study revealedthat the commercial bioremediatorsfailed to remove majority of the totalammoniacal nitrogen when the NH3 levelis high initially.